The Effect of the Combination of Benson Relaxation and Lavender Aromatherapy on Pain in Post Sectio Caesarea Patients - Angriani, Irma; Hartati, Dwi; Risnawati, Risnawati; Sulistyorini, Chandra (Journal of Midwifery and Nursing, 2024)
Sectio caesarea is often associated with post-operative pain due to an incision in the stomach. Handling pain after cesarean section, apart from analgesics, requires non-pharmacological methods, including the Benson relaxation technique, which combines deep breathing relaxation and a person's belief system with lavender aromatherapy, which can release endorphins, thereby relieving pain. In a preliminary study at Dr. Abdul Rivai Hospital, there were ten mothers reporting pain in the area of ??the post-caesarean incision in the abdomen who had never used relaxation techniques, including Benson relaxation and lavender aromatherapy. This study aimed to determine the effect of Benson relaxation and lavender aromatherapy on pain in post-cesarean section patients. This study used pre-experimental and Group Pre-Test – Post-Test Design. A sample of post sectio caesarea patients became 38 people at Dr Abdul Rivai Hospital Berau. The instrument used the NRS scale. Data analysis used the Wilcoxon test. This study showed before being given the combination of Benson relaxation and lavender aromatherapy, the majority of post-cesarean section patients experienced severe pain, 76.3%, and after being given the combination of Benson relaxation and lavender aromatherapy, the majority of post-cesarean section patients experienced mild pain, 86.8%. Combining Benson relaxation and lavender aromatherapy affected pain in post-cesarean section patients (p-value = 0.000). This indicates that the combination of Benson relaxation and lavender aromatherapy is a non-pharmacological therapy that can reduce pain in post-cesarean section patients.